2000
DOI: 10.1023/a:1003965025727
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: SummaryThis study quantified the magnitude of heterosis in pearl millet (Pennisetum glaucum) topcross hybrids produced by crossing 16 diverse landraces and three high yielding open-pollinating varieties on two homozygous malesterile lines. Hybrids and pollinators were grown in 12 year × location combinations in India that were grouped into three zones. Genetic components of variance quantifying the differences among these hybrids were estimated. The hybrids showed a conspicuous heterosis for grain yield, earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Br.] (Yadav, Weltzien-Rattunde, Bidinger, & Mahalakshmi, 2000) and maize (Makumbi, Betrán, Bänziger, & Ribaut, 2011). In rice, QTL responsible for enhanced yield under drought have been mapped and used to improve the rice mega variety IR64 (Swamy et al, 2013).…”
Section: Crop Sciencementioning
confidence: 99%
“…Br.] (Yadav, Weltzien-Rattunde, Bidinger, & Mahalakshmi, 2000) and maize (Makumbi, Betrán, Bänziger, & Ribaut, 2011). In rice, QTL responsible for enhanced yield under drought have been mapped and used to improve the rice mega variety IR64 (Swamy et al, 2013).…”
Section: Crop Sciencementioning
confidence: 99%
“…On the other hand, population hybrids exploit a relatively small part of the total heterosis. Topcross hybrids are also stable, exploit more heterosis than population hybrids, and have already proven their value in harsh drylands (Bidinger et al, 1994;Yadav et al, 2000;Gemenet et al, 2014). Nevertheless, a large-scale, multienvironment stability study comparing populations and topcross and single-cross hybrids in a genetically balanced setup is necessary to find the best option for WA.…”
Section: Prospects and Recommendations For Future Pearl Millet Hybridmentioning
confidence: 99%
“…The yield potential of pearl millet is substantially dependent on the heterozygosity of the genotypes, which can be influenced by breeding open-pollinated, synthetic, and hybrid varieties. Several studies on Indian and West African pearl millet have shown superiority of hybrid varieties compared with population varieties (Burton and Powell, 1968;Bidinger et al, 1994;Ouendeba et al, 1995;Yadav et al, 2000). In hybrid breeding, development of heterotic groups is a basic requirement for efficient breeding of highly heterozygous, well-adapted hybrid varieties.…”
Section: Usefulness Of the Present Data For Heterotic Groupingmentioning
confidence: 99%